2003
DOI: 10.1039/b212830f
|View full text |Cite
|
Sign up to set email alerts
|

Observation and analysis of single DNA nano-kinetics by pin-fiber video scope

Abstract: The nano-kinetic movement of a single DNA molecule was observed and analyzed by a newly developed video-microscope system with an optical fiber, called a pin-fiber video scope. A single lambda-DNA molecule was put in focus using fiber-illumination, and the stretching and shrinking motion was measured. The molecule's kinetics were analyzed by numerical calculations and are discussed. A photocleavage phenomenon of DNA molecules was also visualized by the pin-fiber video scope. The new video-microscope system has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In conclusion, we investigated the types of dyes and oxygen scavenging methods suited to long-term fluorescent observations of DNA molecules by making fluorescent measurements of single DNA molecule observations under diverse conditions. We found YOYO-1 was superior to YOPRO-1 in terms of long-term fluorescent observations, however, it is known that YOYO-1 undergoes photocleavage of DNA molecules when being irradiated by light; 22,29 this would prevent researchers from the long-term observation of DNA molecules. In terms of adoption as a fluorescent dye, consideration should be given not only to photobleaching but also to the photocleavage of DNA molecules.…”
mentioning
confidence: 67%
“…In conclusion, we investigated the types of dyes and oxygen scavenging methods suited to long-term fluorescent observations of DNA molecules by making fluorescent measurements of single DNA molecule observations under diverse conditions. We found YOYO-1 was superior to YOPRO-1 in terms of long-term fluorescent observations, however, it is known that YOYO-1 undergoes photocleavage of DNA molecules when being irradiated by light; 22,29 this would prevent researchers from the long-term observation of DNA molecules. In terms of adoption as a fluorescent dye, consideration should be given not only to photobleaching but also to the photocleavage of DNA molecules.…”
mentioning
confidence: 67%
“…The authors found that interference patterns of laser speckles on a single human living cell was easily recognized using a ''pin-fiber video microscope'' system we had developed. 6,7) Although human tissue and plant tissue observations have been reported to date, [8][9][10] to our knowledge, this is the first report of a single living human cell observation by laser speckle microscopy. In the experiment, it was found that by comparing a living cell with a fixed (dead) cell, the fluctuation activities of their laser speckle patterns were completely different.…”
mentioning
confidence: 95%
“…The experimental setup was fundamentally identical to that in the pin-fiber video microscope system we had already reported. 6,7) Figure 1 shows a simple schematic of the apparatus. The sample on the stage of the microscope (Zeiss, Axioplan) was illuminated using a laser (Crystalaser, Model BCL-005-M, 5 mW, 473 nm, 0.1 nm linewidth, linear polarization) beam propagated through an optical fiber (Thorlabs, SM500).…”
mentioning
confidence: 99%